Kompleksitas Kesetaraan Gender di Indonesia Menuju Era Society 5.0 - Defyanti Khairunnisak; Bima Bustanul Lutfi; Didit Pramudita Darma Putra (Yayasan Literasi Sains Indonesia, 2023)
Gender is a word that comes from Latin which is nothing but a genus which has the meaning of type or type. There are many meanings or understandings about gender, very complicated but the simple meaning of gender is behavior or traits that are attached to men and women who are formed in social groups. in various places, therefore gender is not tied to a region or period. In fact, gender is determined by society and the habits of a region, but gender is determined by God, so it can be concluded that gender and sex are different things and two things that are not the same, so gender can be is defined as the characteristics and roles inherent in men and women as a result of the behavior of the surrounding society in which the man or woman lives, even though gender and sex are different things, having a gender equality relationship is still a taboo, especially for women, there are still many injustices that occur There are still many Indonesian people's mindset that women are only for wives and cannot go to high school. This kind of mindset must be eliminated.